Concretos refratários avançados com alto teor de carbono - Luz, Ana Paula da (Universidade Federal de São Carlos, 2010)
Refractory castables in the Al2O3-SiO2-SiC-C system are applied in the iron making process, including runners for molten slags and metals. Over the past years, several attempts to increase the carbon content of these materials have been performed, aiming to attain good performance when in contact with slags and bath, due to the low wettability of the carbon particles. However, carbon is highly vulnerable to oxidation. Therefore some actions, such as the use of antioxidants, are necessary to keep this element in the refractory microstructure during service. In this work the main objective is the design and development of castable formulations in the system Al2O3-SiO2-SiC-C containing 7 and 10 wt% of a mixture of carbon sources (pitch, coke and carbon black). Besides that, the evolution of the refractories reactions, associated to the use of one of the following antioxidants (Si, B4C and sodium borosilicate glass) or their combination, was investigated by several experimental and practical (i.e. application of one composition on a tilting runner in a metallurgical company) tests and by the thermodynamic simulations developed in the FactSage® software. The wettability technique, using the sessile drop method, was also applied in the evaluation of the interactions between slags and the castables. It was verified that the combined use of three antioxidants resulted in lower oxidation and excellent thermo-mechanical properties for the designed castables. However, when one of the compositions were applied in a tilting runner equipment, a superior mass loss was observed due to the refractory peeling. The excessive sintering of some parts of the castable (and the chemical corrosion at the contact with molten metal/slag led to the wearing of this material. Additionally, thermodynamic calculations pointed out that the Al4O4C, Al2OC, TiO2, and other antioxidants are good options for the refractory system investigated in this work.
Advanced high carbon-containing refractory castables
Keywords: Materiais refratários; Concretos refratários; Carbono; Oxidação; Molhabilidade; Termodinâmica - simulação por computador; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA